A Neglected Medieval Helmet from Lucera in Italy - D’Amato, Raffaele; Negin, Andrey Evgenevich (Studia Ceranea, 2022)
The authors of the present article intend to draw the attention of the scientific community to a Medieval Great Helm found in Lucera, southern Italy, at the end of 1980, and presently unpublished. The importance of the helmet – belonging to the last quarter of 13th century and being one of the older specimens of that category existing in the world – has been until now neglected, and it is the intention of the authors to produce an initial analysis of the helmet, its history, technical characteristics and historical background.